Potential of agroindustrial waste for the synthesis of activated carbon: a review - Vidal Mejia, Mari Victoria (Scientia et Technica, 2018)
In the present article, a review is made of the use of agro-industrial waste and its potential use as a raw material for the manufacture of activated carbons and the various applications in which they can be used. The lignocellulosic biomasses found have a high content of organic compounds and low ash content, as very useful characteristics when subjecting the residues to differentes activations mechanisms (physical or chemical). In addition, the advantages in terms of efficiency and costs, also, the differents applications such as: removal of heavy metals, adsorption of different dyes, elimination of emerging pollutants, uptake of polluting gases, water purification, among others. The study of the analyzed works allows to conclude that the different types of biomasses are useful for the synthesis of activated carbon and that the activation mechanism is the primordial stage of the l process to establish chemical and textural characteristics on the final product